Knowledge, Perception, and Use of Cannabis Therapy in Patients with Inflammatory Bowel Disease - Muñiz-Camacho, Luis A.; Negrón-Quintana, Frances I.; Ramos-Burgos, Luis A.; Cruz-Cruz, Jorge J.; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2021)
Objective: In 2017, the government of Puerto Rico legalized medical cannabis for several conditions including Crohn’s disease (CD). There is little information about cannabis use in this population. This study aimed to develop a demographic characterization and evaluate patient perception on cannabis use for Inflammatory Bowel Disease (IBD) at the University of Puerto Rico Center for Inflammatory Bowel Diseases. Methods: One hundred patients of ages 21 or older with a confirmed diagnosis of IBD were recruited to complete a voluntary anonymous questionnaire. Results: 27% of the surveyed participants reported use of cannabis. Of these, 39% reported moderate knowledge and 53% reported little to no knowledge of medical cannabis. The majority did not discuss cannabis use with their physician (78%), and most saw improvement of their symptoms (68%). Conclusion: Cannabis is frequently considered by patients as a treatment option for IBD but most have limited knowledge about its use. The low number of patients that discuss cannabis use with their physician suggests the need for physician awareness of unreported use. It should also lead to the development of strategies for patient orientation regarding the uses, properties, and expectations of cannabis as a therapy.